(untitled) (International Journal of Environmental Sciences, 2025)
Currently, smart buildings can connect humans to their built environment, which allows for creating sustainable buildings that are sensitive to users’ behavioral and physical requirements to improve human well-being. Recent years have seen the emergence of the notion of "Neuroarchitecture," which combines the fields of neuroscience and architecture to design spaces that satisfy four fundamental aspects of human well-being. Through this, we are better able to comprehend how architecture may influence our well-being on several levels: physically the body, cognitively the brain, emotionally the emotions, and socially the behavioral. The present research aimed to do a comprehensive review on "neurological architecture," encompassing an elucidation regarding the idea, its foundational principles, diverse terms, structural attributes, and its effects on people. The current research employed a qualitative approach wherein researchers collected publications on neurological architecture. Published during the last decade. Subsequently, they developed a systematic review by employing descriptive, theme, narrative, and critical analytic techniques. The authors suggested and discussed a model called "Neuro-architecture" based on the articles chosen from the body of research. In conclusion, the physiological, psychological, cognitive, and behavioural impacts of architecture demonstrated via experiments using neuroarchitecture were presented in a manner that corresponded to the qualities of the design.